1999
DOI: 10.1046/j.1365-313x.1999.00553.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the unconventional myosin VIII in plant cells and its localization at the post‐cytokinetic cell wall

Abstract: SummaryMyosins are a large superfamily of motor proteins which, in association with actin, are involved in intracellular motile processes. In addition to the conventional myosins involved in muscle contractility, there is, in animal cells, a wide range of unconventional myosins implicated in membrane-associated processes, such as vesicle transport and membrane dynamics. In plant cells, however, very little is known about myosins. We have raised an antibody to the recombinant tail region of Arabidopsis thaliana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
173
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(191 citation statements)
references
References 58 publications
18
173
0
Order By: Relevance
“…The use of antibodies with more defined specificity has been realized in only a few studies. Organelle targeting was observed for antibodies raised against a 170-kDa myosin from pollen tubes (15), and Arabidopsis thaliana myosin 1, a class VIII myosin, has been localized to plasmodesmata and maturing cell plates (16)(17). Recent in vitro motility studies of a higher plant myosin XI reveal unique physical properties with very fast movement along F-actin (18).…”
Section: Carola Holweg* and Peter Nickmentioning
confidence: 99%
“…The use of antibodies with more defined specificity has been realized in only a few studies. Organelle targeting was observed for antibodies raised against a 170-kDa myosin from pollen tubes (15), and Arabidopsis thaliana myosin 1, a class VIII myosin, has been localized to plasmodesmata and maturing cell plates (16)(17). Recent in vitro motility studies of a higher plant myosin XI reveal unique physical properties with very fast movement along F-actin (18).…”
Section: Carola Holweg* and Peter Nickmentioning
confidence: 99%
“…Reciprocal stimulation between dimerization via the coiled-coil domains of MYA1 and organelle binding was suggested (Li and Nebenfü hr, 2008a). As for myosin VIII, immunostaining studies showed that it localized to the cell periphery at plant-specific structures such as plasmodesmata and cytokinetic cell plates (Reichelt et al, 1999;Baluska et al, 2001). Recent data from our laboratory and from others confirmed the presence of myosin VIII in plasmodesmata (Golomb et al, 2008) and the cell plate (Van Damme et al, 2004) and further provided evidence for its involvement with endocytosis (Golomb et al, 2008;Sattarzadeh et al, 2008) and its colocalization with the ER (Golomb et al, 2008).…”
mentioning
confidence: 70%
“…The ATM1 clone was kindly provided by Dieter Volkmann from the University of Bonn (Reichelt et al, 1999). The fragments were cloned into the plasmid pART7 downstream to eGFP, with a linker of 10 Ala amino acids between the restriction sites KpnI and BamHI, beside myosin fragments XI-A, XI-D, and XI-G, which were cloned between KpnI and XbaI, and XI-H, which was cloned between KpnI and ClaI.…”
Section: Generation Of Iq Tail and Tail Constructsmentioning
confidence: 99%
“…7). We speculate that the inhibitory mechanism involves interference with class XI myosins; nevertheless, class VIII myosins may also have a role, since they are associated with PD (Reichelt et al, 1999;Volkmann et al, 2003;Golomb et al, 2008). Although specific inhibition of class VIII myosin cargo binding was reported to have no effect on the targeting of the TMV MP to PD (Avisar et al, 2008a), inhibiting the translocation of this myosin class along actin filaments could still lead to hindrance in the cellular pathway that supports the spread of infection.…”
Section: Discussionmentioning
confidence: 95%